Implementación de un sistema de comunicación mediante protocolo Modbus Rtu para la obtención de parámetros eléctricos de una estación fotovoltaica de 3kw - Quinga Loya, Danilo Iván (2022)
The photovoltaic system installed in the laboratory of renewable energies of the Technical University of Cotopaxi does not have a data acquisition system that helps to define the production of electrical energy, for this reason a system for the acquisition of data through MODBUS RTU protocol is developed. The first point is the analysis of information about the automation pyramid, industrial networks, communication networks, topologies of a communication network, the OSI model (ISO7498), the MODBUS RTU communication protocol, RS485 interface and SCADA systems. This information gathering allows to continue with the design stage of the project. In the design of the system, the site and the elements that make up the photovoltaic station are evaluated, thus obtaining the total installed power of the system, the selection of the instruments that will make up the communication system, and also the distribution of the site, the connection plans, the assembly of the equipment, hardware and software configurations.